Analysis of land suitability for mangrove rehabilitation in Bulakbaru Coastal Area, Kedung, Jepara - Setiyowati, Desti; Mustofa, Arif; Kursistiyanto, Nurcahyo (Universitas Malikussaleh, 2025)
Mangrove forests are vital ecosystems that maintain coastal environmental balance by preventing erosion, absorbing waste, providing habitat for aquatic life, and protecting coastlines from natural disasters. However, mangrove areas have been damaged due to land conversion and development. Rehabilitation is necessary, including in Bulakbaru Village, Kedung District, Jepara Regency, through land suitability analysis. This study aims to analyze the suitability of the Bulakbaru coastal area by considering biophysical factors such as tidal patterns, current speed, wave height, sediment particle size, salinity, temperature, and coastal slope. Surveys were conducted at three observation stations, and the data were analyzed using a ranking method based on oceanographic parameters. The results show that Station I has the highest suitability score (92.11%), supported by slow currents, low waves, and fine sediment particles, ideal for mangrove species such as Rhizophora spp. and Avicennia spp. Station III is considered suitable (79.15%), although sediment particles are sandy and stronger currents slightly reduce its suitability. Station II is moderately suitable (77.58%) due to gravelly substrate and strong currents, which limit mangrove growth. Overall, most land in Bulakbaru is deemed suitable for mangrove rehabilitation, particularly Station I, which is the most optimal. Oceanographic factors significantly influence land suitability, with muddy land and slow currents providing ideal conditions for mangrove growth.Keywords: Land Suitability; Mangroves; Rehabilitation